Я не хотела убивать: [роман] / Б. К. Седов - Седов Борис Константинович (Воровской закон, 2004)
Экземпляры: аб. (20181115) / Инвентарный номер: 58956 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 28 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44